Design of an optical lens combined with a total internal reflection (TIR) freeform surface for a LED front fog lamp. (February 2017) - Wang, Hong; Li, Xiufeng; Ge, Peng
Abstract: We propose a design method of an optical lens combined with a total internal reflection (TIR) freeform surface for a LED front fog lamp. The TIR freeform surface controls the edge rays of the LED source. It totally reflects the edge rays and makes them emit from the top surface of the lens. And the middle rays of the LED source go through the refractive surface and reach the measured plane. We simulate the model by Monte Carlo method. Simulation results show that the front fog lamp system can satisfy the requirement of ECE R19 Rev7. The light control efficiency can reach up to 76%. Highlights: We propose an optical lens combined with a total internal reflection for a LED front fog lamp. The TIR freeform surface controls the edge rays of the LED source. Simulation results show that the front fog lamp system can satisfy the requirement of ECE R19 Rev7. Optical efficiency can reach up to 76%.